2001
DOI: 10.1021/ma001266t
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure Characterization of Hyperbranched Polyesteramides

Abstract: The molecular structure of a series of hyperbranched polyesteramides was studied using size exclusion chromatography (SEC), mass spectrometry (MS) and small-angle neutron scattering (SANS). Products with increasing molecular mass were obtained through the polycondensation of in situ produced AB 2-like monomeric units. Electrospray ionization MS indicates that narrow SEC fractions consist of different isomers, the number of which increases with molecular mass. Molecular mass moments and polydispersity numbers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
2
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 34 publications
4
60
2
3
Order By: Relevance
“…Obviously, the hyperbranched macromolecules form very compact structures in both solvents. The slopes can be compared to the results by Gelade et al 11 and de Luca et al, 12 who found slopes of 0.6 and 0.4, respectively. In the latter cases organic solvents were studied.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Obviously, the hyperbranched macromolecules form very compact structures in both solvents. The slopes can be compared to the results by Gelade et al 11 and de Luca et al, 12 who found slopes of 0.6 and 0.4, respectively. In the latter cases organic solvents were studied.…”
Section: Resultsmentioning
confidence: 81%
“…Gelade et al 11 and de Luca et al 12 reported SANS experiments on fractionated hyperbranched poly-(ester amide)s and polyesters in organic solvents. They † GKSS Research Centre.…”
Section: Introductionmentioning
confidence: 99%
“…By use of the appropriate values, large numbers (5ϫ10 6 to 1ϫ10 7 ) of different structures were generated at target DBs of 0.4, 0.6, and 0. For each N and DB value, structures with W values corresponding to the maximum in the distribution and two additional structures on either side of the maximum at onefourth the intensity of the maximum were saved for simulation.…”
Section: ͑24͒mentioning
confidence: 99%
“…Within other efforts, a monotonic increase of ͓ ͔ with N more akin to the Mark-Houwink behavior of linear polymers was observed, regardless of the degree of branching. [7][8][9][10] The conflicting message of these measurements may in part be due to the difficulty associated with characterizing these materials using size exclusion chromatography ͑SEC͒. The noted polydispersities in N and DB complicate the interpretation of SEC applied to HPs since a highly branched molecule with a large value of N can have the same hydrodynamic volume as a less branched or linear molecule with a smaller value of N.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the application of mathematical models, the results of the analytical work confirmed that the ideas of the chemists indeed gave full control over the structures as described above. We published the work in the form of two extensive articles, 11,12 which unexpectedly also yielded us the annual DSM Publication Award (Fig. 6).…”
Section: Structures and Propertiesmentioning
confidence: 99%